Defending Women's Legal Rights through Organizations in Turkey - Ahdiyatul Hidayah; Ahmad Bunyan Wahib (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Turkey is a progressive country in defending women's rights. So to achieve equal rights they have to fight not easily. This research focues on the renewal of women's rights to obtain the same rights as men through various women's movements. This study aims to find out the extent of the journey of the women's movement to get equal rights with men. This research uses an approach to the social movements integration, which is a theory that prioritizes rational attitudes so that an action is an organized collective. The results showed that the women's movement in Turkey are almost gave up because it was not considered by the State. They only considered to play a role in the household, so women had no other rights. It was this factor that eventually gave rise to various women's movements, confidently and supporting each other with a journey that was not easy, finally, women got equal rights as men had rights.